Cooperative design, visualization, and engineering 8th International Conference, CDVE 2011, Hong Kong, China, September 11-14, 2011. Proceedings - Luo, Yuhua (Lecture notes in computer science, 2011)
This book constitutes the refereed proceedings of the 8th International Conference on Cooperative Design, Visualization, and Engineering, CDVE 2011, held in Hong Kong, China, in September 2011. The 33 revised full papers presented were carefully reviewed and selected from numerous submissions. The papers address all aspects of distributed computing, and were organized in topical sections on cooperative design, cooperative applications, cooperative engineering, cooperative visualization, and basic theory and technology.